PERAN NABI DALAM PEMBENTUKAN AKHLAK DAN MORAL MASYARAKAT - Satrio Abdillah; Ardian Al Hidaya; Khoirunnisa; Ardina Panggabean (Yayasan Baitul Hikmah al-Zain, 2025)
The purpose of this study is to analyze the role of the Prophet in the formation of morals and ethics of society through the teachings and examples left behind. This study uses a literature study methodology by reviewing various sources, including religious texts, history books, and scientific articles that discuss the role of the Prophet as a moral guide. The results of the study indicate that the Prophet’s teachings significantly influence the formation of positive moral values in society. The example given by the Prophet in everyday life, both in personal and social aspects, creates a foundation for the development of good morals. In addition, the influence of the Prophet in spreading the values of justice, compassion, and tolerance has been shown to strengthen social cohesion and reduce conflict in society. These findings emphasize the importance of deepening understanding of the Prophet’s teachings to build better morals and ethics in the modern era.